Climate change in Europe between 90 and 50 kyr BP and Neanderthal territorial habitability - Anna Degioanni; Sandrine Cabut; Silvana Condemi; Robin S. Smith (PLoS ONE, 2025)
After having lived as the dominant human species in Europe for over 200 kyr, Homo neanderthalensis (the Neanderthals) disappeared around 40 kyr BP (Before Present) Higham T (2014). Competition with Homo sapiens, who arrived in Europe around the same time, is often invoked to explain this extinction. Others have argued that climate change may have reduced the living space of this population making its disappearance more rapid. In order to test the climate change hypothesis we modelled the Neanderthals’ ecological niches in Europe between 90 and 50 kyr BP through paleoenvironmental reconstructions and Eco-Cultural Niche Modelling. We selected five environmental variables (orographic height, mean annual precipitation, mean temperature of the coldest month, carrying capacity and friction, see below) from climate model simulations of 5 periods between 90 and 50 kyr BP in Europe. We used Structural Similarity (SSIM) index to compare the probability maps of suitable niches to Neanderthals performed by Maxent. After a strong initial environmental change between the first (P1 = 90 to 83 kyr BP) and second (P2 = 83 to 69 kyr BP) periods, our results show that large areas highly suitable for Neanderthal occupation persisted across Europe. As our results show an increase/stability of the areas suitable to Neanderthals, the question of the cause of the decrease or displacement of the Neanderthal population towards southern Europe after this climatic change remains open.